Sérialités serrées - Cheyenne Olivier (Strenae)
This article explores the creative challenges in the creation of a series of children’s picture books. While literary series have recently been the objects of a growing body of studies, there remain few inquiries on that topic in the field of children’s literature and picturebooks. The focus on reception often primes over the study of the creative strategies operated by authors and illustrators in the conception process. This article focuses on a genetic analysis of an ongoing series of ten picture books about poverty co-created with Esther Duflo and published at Le Seuil Jeunesse in 2022 and 2023. The results show that the illustrator first establishes structural principles that systematically anchor the series’ many evolutions. Its persistence in the long-term relies on well established closing mechanisms and the setting-up of a dense linking between its growing extensions. Unlike the reader’s perception of an ever-expanding world, the illustrator’s experience of a series consists in the constant tightening of his creation.